Ketimpangan Wilayah Antar Kabupaten/Kota di Provinsi Lampung - Heru Wahyudi; Farida Aliyatul Asy’ariati (Penerbit Goodwood, 2021)
Purpose: The purpose of the study was to determine the regional inequality of districts/cities in Lampung Province before and during the COVID-19 pandemi. Research methodology: The analytical tool used in this research is quantitative descriptive analysis method. In conducting this research, the researcher used the help of the Microsoft Excel 2010 analysis tool. Results: The Williamson index of districts/cities in Lampung Province throughout the 2016-2019 period has increased every year. The index value in 2016 was 0.26, increasing to 0.28 in 2017, 2018 and 2019 reaching 0.32, while regional inequality in 2020 also increased in 2021 to 0.27. Theoretically, the gap rate is still at a low level of economic disparity between regions (less than 0.35). Limitations: The limitation in this study is to use quantitative analysis without looking at the effect of independent variables on inequality (without regression analysis). Contribution: The results obtained from this study are expected to be one of the references in making policy directions based on the data presented to adjust the right policies, especially to reduce inequality between regencies/cities in Lampung Province, through efforts to reduce the number of poor people.